Proceedings of the 13th Annual ACM International Workshop on Geographic Information Systems 2005
DOI: 10.1145/1097064.1097093
|View full text |Cite
|
Sign up to set email alerts
|

Efficient query processing on spatial networks

Abstract: A framework for determining the shortest path and the distance between every pair of vertices on a spatial network is presented. The framework, termed SILC, uses path coherence between the shortest path and the spatial positions of vertices on the spatial network, thereby, resulting in an encoding that is compact in representation and fast in path and distance retrievals. Using this framework, a wide variety of spatial queries such as incremental nearest neighbor searches and spatial distance joins can be show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
97
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 40 publications
0
97
0
2
Order By: Relevance
“…In our examples, the sorting supported operations that involve proximity measured in terms of as "the crow flies". However, these representations can also be used to support proximity in a graph such as a road network (e.g., (Sankaranarayanan et al, 2005;Samet et al, 2008)). …”
Section: Discussionmentioning
confidence: 99%
“…In our examples, the sorting supported operations that involve proximity measured in terms of as "the crow flies". However, these representations can also be used to support proximity in a graph such as a road network (e.g., (Sankaranarayanan et al, 2005;Samet et al, 2008)). …”
Section: Discussionmentioning
confidence: 99%
“…The drawback of this approach is that, for n vertices, the amount of storage could be as high as Oðn 3 Þ. The necessary storage can be reduced to Oðn 2 Þ by taking advantage of the fact that the shortest paths from vertex u to all remaining vertices can be decomposed into subsets based on the first edges on the shortest paths to them from u [9], [10], [11]. The cost is a slower process of retrieving the shortest path which makes use of a sequence of point location operations (e.g., [6]).…”
Section: Introductionmentioning
confidence: 99%
“…The cost is a slower process of retrieving the shortest path which makes use of a sequence of point location operations (e.g., [6]). We have shown that the storage necessary for these subsets can be reduced substantially further to Oðn 1:5 Þ [9], [10], [12] by noting the spatial coherence of the subsets and representing them using a shortest path quadtree, which is a variant of the region quadtree, where the blocks are decomposed until all vertices in the block are in the same subset. Note that the use of the quadtree in that context is primarily to take advantage of its dimension-reducing property [13] to decrease the storage requirements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the database management perspective, efficient LBS support request the integration of several research advances in indexing [13], [17] and query processing techniques [5], [12], [14], [16]. The development of such services has also indicated several open research issues such as the processing of forecasting queries (i.e., determining future positions of moving points [4]), the support of continuous location change in query processing techniques [3], knowledge discovery from data collected via LBS [10], etc.…”
Section: Introductionmentioning
confidence: 99%